ED Triage Process Improvement: Timely Vital Signs for Less Acute Patients. - Falconer, Stella S.; Karuppan, Corinne M.; Kiehne, Emily; Rama, Shravan (Journal of Emergency Nursing, 2018)
Abstract Problem Vital signs can result in an upgrade of patients' Emergency Severity Index (ESI) levels. It is therefore preferable to obtain vital signs early in the triage process, particularly for ESI level 3 patients. Emergency departments have an opportunity to redesign triage processes to meet required protocols while enhancing the quality and experience of care. Methods We performed process analyses to redesign the door-to-vital signs process. We also developed spaghetti diagrams to reconfigure the patient arrival area. Results The door-to-vital signs time was reduced from 43.1 minutes to 6.44 minutes. Both patients and triage staff seemed more satisfied with the new process. The patient arrival area was less congested and more welcoming. Discussion Performing activities in parallel reduces flow time with no additional resources. Staff involvement in process planning, redesign, and control ensures engagement and early buy-in. One should anticipate how changes to one process might affect other processes. Unlabelled Box Contribution to Emergency Nursing Practice • The purpose of this practice improvement initiative was to decrease door-to-vital signs time through a process redesign. • The primary outcome of this practice improvement project was that parallel processing and layout redesign can improve triage efficiency and ensure timely vital signs with no additional resources. • Key implications for emergency nursing practice based on this project are (1) triage staff should be involved early in the redesign process, and (2) process change control is imperative.